2011
DOI: 10.1182/blood-2011-01-330514
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem/progenitor cells, generation of induced pluripotent stem cells, and isolation of endothelial progenitors from 21- to 23.5-year cryopreserved cord blood

Abstract: IntroductionThe first cord blood (CB) transplantation saved the life of a young patient with Fanconi anemia using HLA-matched sibling CB cells, 1 a procedure made possible by identification and cryopreservation of transplantable hematopoietic progenitor cells (HPCs) and hematopoietic stem cells (HSCs) in CB. 2 More than 20 000 CB transplantations have treated the same malignant and nonmalignant disorders as bone marrow (BM). 3-8 CB transplantation is possible because of CB banks, and how long CB can be stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 24 publications
7
140
0
4
Order By: Relevance
“…In fact, clinical trials are now underway in type 1 diabetes, cerebral palsy and peripheral vascular disease. Moreover, recent studies demonstrated that it is possible to generate induced pluripotent stem (iPS) cells from human CB (Giorgetti et al, 2009;Haase et al, 2009;Hu et al, 2011;Broxmeyer et al, 2011). These data offer CB derived iPS cells are also considered an ideal source for future regenerative therapies.…”
Section: Resultsmentioning
confidence: 98%
“…In fact, clinical trials are now underway in type 1 diabetes, cerebral palsy and peripheral vascular disease. Moreover, recent studies demonstrated that it is possible to generate induced pluripotent stem (iPS) cells from human CB (Giorgetti et al, 2009;Haase et al, 2009;Hu et al, 2011;Broxmeyer et al, 2011). These data offer CB derived iPS cells are also considered an ideal source for future regenerative therapies.…”
Section: Resultsmentioning
confidence: 98%
“…Advantages of using neonatal cord blood cells for generating iPSCs include (1) cord blood may contain a fewer number of acquired somatic mutations compared with other adult cell types from the same individuals; (2) a large number of cord blood samples have already been preserved in cord blood banks. Cord blood samples cryopreserved for more than 20 years have been successfully reprogrammed to iPSCs [48]. In addition, we have previously shown that an episomal vectorbased system efficiently reprogrammed unfractionated cord blood cells without the need for enrichment of progenitor cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kordon kanındaki hemotopoetik kök hücrelerin engrafman kapasitesinin kemik iliğindekilerden daha fazla olduğu immünosupresif fare deneylerinde gösterilmiştir 19,20 .…”
Section: Kordon Kanı Hücrelerinin Farklılıklarıunclassified